SIMULATION STUDY OF HYDRODYNAMIC CAVITATION IN THE ORIFICE FLOW - PIETRYKOWSKI, Konrad; KARPIŃSKI, Paweł (Applied Computer Science, 2022)
Hydrodynamic cavitation is a phenomenon that can be used in the water treatment process. For this purpose, venturis or orifices varying in geometry are used. Studying this phenomenon under experimental conditions is challenging due to its high dynamics and difficulties in measuring and observing the phase transition of the liquid. For this reason, the CFD method was used to study the phenomenon of hydrodynamic cavitation occurring in water flow through the orifice and then analyze flow parameters for different boundary conditions. The research was performed for four different orifice geometries and two defined fluid pressure values at the inlet, based on a computational 2D model of the research object created in Ansys Fluent software. As a result of the numerical simulation, the distribution of fluid velocity and pressure and volume fraction of the gas phase were obtained. A qualitative and quantitative analysis of the phenomenon of hydrodynamic cavitation under the considered flow conditions was conducted for the defined orifice geometries. The largest cavitation zone and thus the largest volume fraction of the gas phase was obtained for the orifice diameter of 2 mm with a sharp increase in diameter. However, the geometry with a linear change in diameter provided the largest volume fraction of the gas phase per power unit.